Polyester resin, aqueous resin dispersion and toner
The polyester resin with tailored chemical groups and alkylene oxide adducts improves toner charging performance and stability, overcoming hygroscopicity and blocking issues in electrophotographic processes.
Patent Information
- Application Number
- JP2023066789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-04-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-04-17
AI Technical Summary
Existing toners using polyester resins with sulfonic acid groups for electrophotography suffer from insufficient charging performance due to hygroscopicity, leading to blocking issues and inadequate heat-resistant storage stability.
A polyester resin is developed with carboxylic acid, sulfonic acid, sulfamic acid, and phosphate groups, incorporating alkylene oxide adducts of bisphenol A, with specific molar ratios and glass transition temperatures to enhance chargeability and stability.
The resin provides toners with excellent charging properties and maintains heat-resistant storage stability, addressing the limitations of previous resins.
Smart Images

Figure 0007612743000001 
Figure 0007612743000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin, an aqueous resin dispersion, and a toner. [Background technology]
[0002] 2. Description of the Related Art In recent years, with the development of electrophotographic systems, the demand for electrophotographic apparatuses such as copying machines and laser printers has increased rapidly, and the requirements for their performance have also become more sophisticated. For full-color electrophotography, a method and apparatus have been known in which a latent image based on color image information is formed on a latent image carrier such as an electrophotographic photosensitive member, the latent image is developed with a toner of a corresponding color, and then the toner image is transferred onto a transfer material. After repeating such image forming steps, the toner image on the transfer material is heated and fixed to obtain a multi-color image.
[0003] To pass through these processes without any problems, the toner needs to have good fixability to paper. In addition, since the fixing section of the device has a heater, the temperature rises inside the device, so the toner needs to be free from blocking inside the device.
[0004] In order to achieve the above-mentioned performance, a toner has been proposed that uses an aqueous resin dispersion containing a polyester resin having a sulfonate group, the sulfonate group being a group with a valence of 2 or more (Patent Document 1). However, although the toner using the above-mentioned resin aqueous dispersion has good blocking properties within the device, the chargeability of the toner is not sufficient due to the hygroscopicity of the polyester resin in the toner, and improvements in these areas are desired. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-136707 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a toner that has excellent chargeability while maintaining heat-resistant storage stability. [Means for solving the problem]
[0007] The present inventors conducted extensive research to solve these problems and arrived at the present invention. That is, the present invention relates to a polyester resin obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y), the polyester resin being a polyester resin having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group, the polyester resin including one in which the valence of the base constituting the carboxylate group, the sulfonate group, the sulfamate group, or the phosphate group is 1, the alcohol component (x) contains an alkylene oxide adduct (x1) of bisphenol A, the content of (x1) in (x) being 20 to 40 moles based on the total mole number of (x). 98 mol %, the (x1) contains an ethylene oxide adduct of bisphenol A (x11) and a propylene oxide adduct of bisphenol A (x12), and the molar ratio [(x11) / (x12)] of the ethylene oxide adduct of bisphenol A (x11) to the propylene oxide adduct of bisphenol A (x12) in the (x1) is 30 / 70 to 70 / 30. The glass transition temperature of the polyester resin is 55 to 85° C. a polyester resin; an aqueous resin dispersion in which resin fine particles containing the polyester resin are dispersed in an aqueous medium; and a toner containing the polyester resin and a colorant. Effect of the Invention
[0008] According to the present invention, it is possible to provide a toner that has excellent chargeability while maintaining heat-resistant storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The polyester resin, the aqueous resin dispersion, and the toner of the present invention will be described below in this order.
[0010] The polyester resin of the present invention is a polyester resin obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y), the polyester resin having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group, and includes those in which the valence of the base constituting the carboxylate group, the sulfonate group, the sulfamate group, or the phosphate group is 1, and the alcohol component (x) contains an alkylene oxide adduct (x1) of bisphenol A. By the polyester resin having the above-mentioned base and having the alkylene oxide adduct (x1) of bisphenol A as a constituent, it has a rigid skeleton while retaining an appropriate amount of charge, and therefore a toner with excellent chargeability while maintaining heat-resistant storage stability can be obtained.
[0011] Examples of the alcohol component (x) constituting the polyester resin of the present invention include the alkylene oxide adduct (x1) of bisphenol A, which is an essential component, as well as diols and / or polyols having a valence of three or more other than the alkylene oxide adduct (x1) of bisphenol A, which will be described later. Furthermore, monoalcohols may be used as the alcohol component (x) if necessary.
[0012] The alkylene oxide adduct of bisphenol A (x1) is a compound obtained by adding an alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) to bisphenol A, and the alkylene oxide adduct of bisphenol A (x1) contains an ethylene oxide adduct of bisphenol A (hereinafter, "ethylene oxide" may be abbreviated as EO) (x11) and a propylene oxide adduct of bisphenol A (hereinafter, "propylene oxide" may be abbreviated as PO) (x12) from the viewpoints of electrostatic chargeability and storage stability.
[0013] Examples of the alkylene oxide adduct of bisphenol A (x1) include an ethylene oxide adduct of bisphenol A (x11), which is an essential component, and a propylene oxide adduct of bisphenol A (x12), as well as, for example, a butylene oxide (hereinafter, "butylene oxide" may be abbreviated as BO) adduct of bisphenol A (x13).
[0014] The molar ratio [(x11) / (x12)] of the ethylene oxide adduct of bisphenol A (x11) to the propylene oxide adduct of bisphenol A (x12) in the alkylene oxide adduct of bisphenol A (x1) is 30 / 70 to 70 / 30 from the viewpoints of electrostatic chargeability and storage stability.
[0015] The number of moles of alkylene oxide added in the alkylene oxide adduct of bisphenol A (x1) is preferably 2 to 30, more preferably 2 to 10, and further preferably 2 to 5, from the viewpoints of chargeability and storage stability.
[0016] Diols other than the alkylene oxide adduct of bisphenol A (x1) include alkylene glycols having 2 to 12 carbon atoms (e.g., ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, propylene glycol, 1,2-butanediol, 1,2-pentanediol, 1,2-hexanediol, 1,2-heptanediol, 1,2-octanediol, 1,2-nonaphthalene diol, and the like. 1,2-decanediol), alkylene ether glycols having 4 to 36 carbon atoms (e.g., diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.), alicyclic diols having 4 to 36 carbon atoms (e.g., 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.), alkylene oxide [EO, PO, BO, etc.] adducts of the above alicyclic diols (preferably or an adduct of bisphenols (bisphenol F, bisphenol S, etc.) with alkylene oxides (EO, PO, BO, etc.) (preferably an adduct of 2 to 30 moles), polylactone diols (poly-ε-caprolactone diol, etc.), polybutadiene diols, diols having a sulfonic acid group and / or a sulfonate salt group (for example, 3-(2,3-dihydroxypropoxy)-1-propanesulfonic acid, 3,4-dihydroxybutanesulfonic acid, 3,6-dihydroxy- 2-toluenesulfonic acid, etc.), diols having a sulfamic acid group and / or a sulfamic acid group (for example, N,N-bis(2-hydroxyethyl)sulfamic acid, N,N-bis(2-hydroxyethyl)sulfamic acid PO 2 mole adduct, etc.), and diols having a phosphoric acid group and / or a phosphoric acid group (a reaction product of a hydroxyl group of a polyol having a valence of three or more described below with phosphoric acid or an acidic phosphoric acid ester (a phosphoric acid mono- or diester having an alkyl group having 1 to 12 carbon atoms)).
[0017] Examples of polyols with a valence of three or more include polyhydric aliphatic alcohols having a valence of three or more and having 3 to 36 carbon atoms, AO adducts of polyhydric aliphatic alcohols (number of moles added: 2 to 120), AO adducts of trisphenols (trisphenol PA, etc.) (number of moles added: 2 to 30), AO adducts of novolak resins (phenol novolak, cresol novolak, etc.) (number of moles added: 2 to 30), and acrylic polyols [copolymers of hydroxyethyl (meth)acrylate and other vinyl monomers, etc.]. Examples of the trihydric or higher polyhydric aliphatic alcohol having 3 to 36 carbon atoms include alkane polyols and their intramolecular or intermolecular dehydration products, as well as sugars (such as sucrose) and their methyl glucosides. Specific examples of alkane polyols and their intramolecular or intermolecular dehydration products include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, and polyglycerin.
[0018] Examples of monoalcohols include linear or branched alkyl alcohols having 1 to 30 carbon atoms (such as methanol, ethanol, isopropanol, 1-decanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, and lignoceryl alcohol).
[0019] When the alcohol component (x) contains a component other than the alkylene oxide adduct of bisphenol A (x1), from the viewpoints of solubility and electrostatic chargeability of the polyester resin, diols and polyols having a valence of three or more are preferred, alkylene glycols having 2 to 12 carbon atoms and polyhydric aliphatic alcohols having a valence of three or more carbon atoms are more preferred, and polyhydric aliphatic alcohols having a valence of three or more carbon atoms are particularly preferred.
[0020] Since the polyester resin of the present invention is a polyester resin having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group, from the viewpoint of introducing a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group into the polyester resin, it is more preferable that the alcohol component (x) contains the above-mentioned diol having a sulfonic acid group and / or a sulfonate group, diol having a sulfamic acid group and / or a sulfamate group, or diol having a phosphate group and / or a phosphate group.
[0021] The carboxylic acid component (y) of the polyester resin may be a dicarboxylic acid and / or a polycarboxylic acid having a valence of 3 or more, an anhydride of these acids, or a lower alkyl (having 1 to 4 carbon atoms) ester (e.g., methyl ester, ethyl ester, isopropyl ester, etc.). If necessary, a monocarboxylic acid may be used as the carboxylic acid component (y).
[0022] Examples of dicarboxylic acids include alkanedicarboxylic acids having 2 to 50 carbon atoms {alkanedicarboxylic acids having carboxyl groups at both ends of a chain saturated hydrocarbon group (succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,18-octadecanedicarboxylic acid, etc.), alkanedicarboxylic acids having a carboxyl group at a terminal other than the end of a chain saturated hydrocarbon group (decylsuccinic acid, etc.)}, alkenedicarboxylic acids having 4 to 50 carbon atoms (alkenylsuccinic acids such as dodecenylsuccinic acid, pentadecenylsuccinic acid, octadecenylsuccinic acid, maleic acid, fumaric acid, citraconic acid, etc.), alicyclic dicarboxylic acids having 6 to 40 carbon atoms [dimer acids (dimerized linoleic acid, aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, t-butylisophthalic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, etc.), dicarboxylic acids having a sulfonic acid group and / or a sulfonate group (4-sulfoisophthalic acid, 5-sulfoisophthalic acid, 2-sulfoterephthalic acid, sodium dimethyl isophthalate-5-sulfonate, and sulfosuccinic acid), and dicarboxylic acids having a sulfamic acid group and / or a sulfamate group (N-[2,3-dicarboxyphenyl]sulfamic acid and N-[2,4-dicarboxyphenyl]sulfamic acid).
[0023] Examples of polycarboxylic acids having a valence of three or more include aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid), aliphatic tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid), and vinyl polymers of unsaturated carboxylic acids [number average molecular weight (Mn): 450 to 10,000] (such as styrene / maleic acid copolymers, styrene / acrylic acid copolymers, and styrene / fumaric acid copolymers).
[0024] Examples of monocarboxylic acids include aromatic monocarboxylic acids having 7 to 37 carbon atoms (including the carbon of the carbonyl group) (benzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, etc.), and aliphatic monocarboxylic acids having 2 to 50 carbon atoms (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, behenic acid, (meth)acrylic acid ["(meth)acrylic" means acrylic or methacrylic], crotonic acid, isocrotonic acid, cinnamic acid, etc.).
[0025] Since the polyester resin of the present invention is a polyester resin having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group, from the viewpoint of introducing a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group into the polyester resin, the carboxylic acid component (y) preferably contains the above-mentioned dicarboxylic acids, polycarboxylic acids having a valence of three or more, acid anhydrides thereof, and lower alkyl esters thereof, and more preferably contains a dicarboxylic acid having a sulfonic acid group and / or a sulfonate group.
[0026] Among polyester resins having at least one group selected from the group consisting of carboxylate, sulfonate, sulfamate and phosphate groups, polyester resins having carboxylate and / or sulfonate groups are preferred from the viewpoints of chargeability and ease of introduction. The carboxylate, sulfonate, sulfamate and phosphate groups may be introduced into the polyester resin by using a component having at least one group selected from the group consisting of carboxylate, sulfonate, sulfamate and phosphate groups in the alcohol component (x) or the carboxylic acid component (y), or may be introduced into the polyester resin by using a component having a carboxylate, sulfonate, sulfamate and phosphate group to obtain a polyester resin having at least one group selected from the group consisting of carboxylate, sulfonate, sulfamate and phosphate groups, and then reacting the acid with a base described below.
[0027] From the viewpoint of chargeability, the valence of the base constituting the carboxylate group, sulfonate group, sulfamate group or phosphate group in the present invention includes those having a valence of 1. Examples of the base having a valence of one include ammonia, monoamines having 1 to 30 carbon atoms, quaternary ammonium, and alkali metals (lithium, sodium, potassium, etc.). Examples of monoamines having 1 to 30 carbon atoms include primary and / or secondary amines having 1 to 30 carbon atoms (ethylamine, n-butylamine, isobutylamine, etc.) and tertiary amines having 3 to 30 carbon atoms (trimethylamine, triethylamine, lauryldimethylamine, etc.). Examples of quaternary ammoniums include trialkylammoniums having 4 to 30 carbon atoms (lauryltrimethylammonium, etc.). Among these bases, from the viewpoint of chargeability, alkali metals are preferred, and sodium is more preferred. The polyester resin of the present invention may have a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group, the constituent base of which has a valence of 2 or more (such as alkaline earth metal, aluminum, and polyamine).More preferably, the polyester resin contains only those in which the constituent base of the carboxylate group, the sulfonate group, the sulfamate group, or the phosphate group has a valence of 1.
[0028] From the viewpoint of heat-resistant storage stability, the content of (x1) in (x) of the alcohol component (x) is 20 to 100 mol %, more preferably 40 to 100 mol %, and even more preferably 48 to 98 mol %, based on the total number of moles of (x).
[0029] The content of the component having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group in the carboxylic acid component (y) is preferably 2 to 10 mol %, and more preferably 4 to 8 mol %, based on the total number of moles of (y), from the viewpoints of electrostatic chargeability and heat-resistant storage stability.
[0030] The reaction ratio of the alcohol component and the carboxylic acid component, expressed as the molar ratio of hydroxyl groups to carboxyl groups {[OH] / [COOH]}, is preferably 1 / 2 to 2 / 1, more preferably 1 / 1.5 to 1.5 / 1, and even more preferably 1 / 1.4 to 1.4 / 1. The hydroxyl groups are those derived from the alcohol component.
[0031] In the present invention, the polyester resin can be obtained by mixing an alcohol component (x) containing an alkylene oxide adduct of bisphenol A (x1), a carboxylic acid component (y), and a component containing a raw material constituting a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group, and carrying out a polycondensation reaction in the presence of a polymerization catalyst. Furthermore, when the alcohol component (x) contains an ethylene glycol component, it may be an ethylene glycol component derived from PET (polyethylene terephthalate), and when the carboxylic acid component (y) contains a terephthalic acid component, it may be a terephthalic acid component derived from PET (polyethylene terephthalate). In this case, the polyester resin can be obtained by mixing PET, the alcohol component (x), the carboxylic acid component (y), and a component containing a raw material constituting a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group, and carrying out a polycondensation reaction in the presence of a polymerization catalyst.
[0032] Specifically, the polyester resin can be produced as follows. For example, the polyester resin can be produced by reacting an alcohol component (x), a carboxylic acid component (y), and a raw material that constitutes a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group in an inert gas (nitrogen gas, etc.) atmosphere at a reaction temperature of preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C. The reaction time is preferably 30 minutes or more, more preferably 2 to 40 hours, from the viewpoint of ensuring the polycondensation reaction and emulsion stability. In order to improve the reaction rate, it is preferable to have a pressure reduction step, and the degree of pressure reduction is preferably 0.5 to 20 kPa, more preferably 0.5 to 15 kPa, and even more preferably 0.5 to 10 kPa.
[0033] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxybis(triethanolaminate), titanium dihydroxybis(triethanolaminate), titanium monohydroxytris(triethanolaminate), titanyl bis(triethanolaminate) and their intramolecular polycondensates, etc.}, and catalysts described in JP-A-2007-11307 (titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, titanium diisopropoxyditerephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.), and zinc acetate, etc. Among these, titanium-containing catalysts are preferred.
[0034] In the present invention, the glass transition temperature (Tg) of the polyester resin is preferably 45 to 86° C., more preferably 55 to 85° C., from the viewpoints of heat-resistant storage stability and electrostatic chargeability. The glass transition temperature (Tg) can be measured by the method specified in ASTM D3418-82 (DSC method) using, for example, DSC Q20 manufactured by TA Instruments Co., Ltd.
[0035] In the present invention, the acid value of the polyester resin is preferably 5 to 40 mgKOH / g, more preferably 15 to 35 mgKOH / g, and further preferably 20 to 30 mgKOH / g. The acid value of the polyester resin can be measured by the method specified in JIS K0070 (1992 edition).
[0036] In the present invention, the weight average molecular weight of the polyester resin as measured by gel permeation chromatography (GPC) is preferably 4,000 to 100,000, more preferably 5,000 to 30,000, and particularly preferably 6,000 to 20,000, from the viewpoints of heat-resistant storage stability and dispersibility.
[0037] The weight average molecular weight in the present invention can be measured by gel permeation chromatography (GPC) under the following conditions. Equipment: "HLC-8120" [Tosoh Corporation] Column: "TSK GEL GMH6" [Tosoh Corporation] x 2 Measurement temperature: 40℃ Sample solution: 0.25% by weight tetrahydrofuran solution (insolubles were filtered off using a glass filter) Solution injection volume: 100μl Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weight: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) [manufactured by Tosoh Corporation]
[0038] The resin aqueous dispersion of the present invention is a resin aqueous dispersion in which resin fine particles containing the polyester resin of the present invention are dispersed in an aqueous medium. The aqueous medium is not particularly limited as long as it is a liquid containing water as an essential component, and examples thereof include an aqueous solution in which a surfactant is added to water.
[0039] The method for obtaining an aqueous resin dispersion by dispersing resin fine particles containing a polyester resin in an aqueous medium is not particularly limited, and the following methods (1) to (7) can be mentioned. (1) A method in which a precursor of a polyester resin (monomer, oligomer, etc.) or a solvent solution thereof is dispersed in an aqueous medium in the presence of a suitable dispersant, and then heated to produce an aqueous dispersion of resin fine particles. (2) A method in which a suitable emulsifier is dissolved in a polyester resin precursor (monomer, oligomer, etc.) or its solvent solution (preferably liquid; may be liquefied by heating), and then water is added to cause phase inversion emulsification. (3) A method in which a polyester resin is pulverized using a mechanical rotary or jet type fine pulverizer, and then classified to obtain fine resin particles, which are then dispersed in water in the presence of a suitable dispersant. (4) A method in which a resin solution in which a polyester resin is dissolved in a solvent is sprayed in the form of mist to obtain fine resin particles, and then the fine resin particles are dispersed in water in the presence of a suitable dispersant. (5) A method in which a poor solvent is added to a resin solution in which a polyester resin is dissolved in a solvent, or a resin solution that has been previously heated and dissolved in a solvent is cooled to precipitate resin fine particles, and then the solvent is removed to obtain resin particles, which are then dispersed in water in the presence of a suitable dispersant. (6) A method in which a resin solution obtained by dissolving a polyester resin in a solvent is dispersed in an aqueous medium in the presence of a suitable dispersant, and then the solvent is removed by heating or reducing pressure, etc. (7) A method in which a suitable emulsifier is dissolved in a resin solution obtained by dissolving a polyester resin in a solvent, water is added to cause phase inversion emulsification, and the solvent is then removed by heating or reducing pressure, etc.
[0040] Dispersion in the above methods (1) to (7) can be carried out using a dispersing machine. The dispersing machine is not particularly limited as long as it is a commercially available emulsifying machine or dispersing machine, and examples thereof include batch type emulsifying machines such as Homogenizer (manufactured by IKA), Polytron (manufactured by Kinematica), and TK Auto Homo Mixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), Ebara Milder (manufactured by Ebara Corporation), TK Filmix, TK Pipeline Homo Mixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), Colloid Mill (manufactured by Shinko Pantech Co., Ltd.), Ultra Visco Mill (manufactured by Imex Co., Ltd.), Slasher, To Examples of such emulsifiers include continuous emulsifiers such as Ligonal Wet Mill (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), Capitron (manufactured by Eurotech), and Fine Flow Mill (manufactured by Pacific Machinery Co., Ltd.); high-pressure emulsifiers such as Microfluidizer (manufactured by Mizuho Kogyo Co., Ltd.), Nanomizer (manufactured by Nanomizer Co., Ltd.), and APV Gaulin (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as Membrane Emulsifier (manufactured by Reika Kogyo Co., Ltd.); vibration emulsifiers such as Vibro Mixer (manufactured by Reika Kogyo Co., Ltd.); and ultrasonic emulsifiers such as Ultrasonic Homogenizer (manufactured by Branson).
[0041] In the above methods (1) to (7), the emulsifier or dispersant used in combination may be a known surfactant (s), a water-soluble polymer (t), etc. Also, an organic solvent, a plasticizer, etc. may be used in combination as an emulsifying or dispersing aid.
[0042] The surfactant (s) is not particularly limited, and examples thereof include anionic surfactants (s-1), cationic surfactants (s-2), amphoteric surfactants (s-3), and nonionic surfactants (s-4), etc. The surfactant (s) may be a combination of two or more surfactants.
[0043] Examples of the anionic surfactant (s-1) include carboxylic acids or salts thereof, sulfate salts, salts of carboxymethyl compounds, sulfonates, and phosphate salts. Examples of the cationic surfactant (s-2) include quaternary ammonium salt surfactants and amine salt surfactants. Examples of the amphoteric surfactant (s-3) include carboxylate-type amphoteric surfactants, sulfate-type amphoteric surfactants, sulfonate-type amphoteric surfactants, and phosphate-type amphoteric surfactants. Examples of the nonionic surfactant (s-4) include AO addition type nonionic surfactants and polyhydric alcohol type nonionic surfactants. Specific examples of these surfactants (s) include those described in JP-A-2002-284881.
[0044] Examples of the water-soluble polymer (t) include cellulose compounds (e.g., methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, ethylhydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl cellulose, and saponified products thereof, etc.), gelatin, starch, dextrin, gum arabic, chitin, chitosan, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, polyacrylamide, acrylic acid (salt)-containing polymers (sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, partially neutralized polyacrylic acid with sodium hydroxide, and sodium acrylate-acrylic acid ester copolymers, etc.), sodium hydroxide (partially) neutralized styrene-maleic anhydride copolymers, and water-soluble polyurethanes (polyethylene glycol, and reaction products of polycaprolactone diol, etc. with polyisocyanate, etc.).
[0045] Organic solvents include aromatic hydrocarbon solvents (toluene, xylene, ethylbenzene, tetralin, etc.); aliphatic hydrocarbon solvents (n-hexane, n-heptane, n-decane, mineral spirits, cyclohexane, etc.); halogenated solvents (methyl chloride, methyl bromide, methyl iodide, methylene dichloride, carbon tetrachloride, trichloroethylene, perchloroethylene, etc.); ester solvents (ethyl acetate, butyl acetate, methyl 2-hydroxyisobutyrate, methyl lactate, ethyl lactate, methoxybutyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, methyl pyruvate, ethyl pyruvate, etc.); ether solvents (diethyl ether, tetrahydrofuran, dioxane, dioxolane, ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc.); ketone solvents (acetone, methyl ethyl ketone, methyl isobutyl ketone, di-n-butyl ketone, cyclohexanone, etc.); alcohol solvents (methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, 2-ethylhexyl alcohol, benzyl alcohol, 2,2,3,3-tetrafluoropropanol, trifluoroethanol, etc.); amide solvents (dimethylformamide, dimethylacetamide, etc.); sulfoxide solvents (dimethyl sulfoxide, etc.); heterocyclic compound solvents (N-methylpyrrolidone, etc.), and mixed solvents of two or more of these.
[0046] Examples of plasticizers include phthalate esters (dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, diisodecyl phthalate, etc.); aliphatic dibasic acid esters (di-2-ethylhexyl adipate, 2-ethylhexyl sebacate, etc.); trimellitate esters (tri-2-ethylhexyl trimellitate, trioctyl trimellitate, etc.); phosphate esters (triethyl phosphate, tri-2-ethylhexyl phosphate, tricresyl phosphate, etc.); fatty acid esters (butyl oleate, etc.); and mixtures of two or more of these.
[0047] The volume average particle size of the resin fine particles in the resin aqueous dispersion is preferably from 20 to 500 nm, more preferably from 30 to 200 nm, from the viewpoint of chargeability. The volume average particle size of the resin microparticles can be measured using a laser particle size distribution measuring device such as "LA-920" (manufactured by Horiba, Ltd.) or "Multisizer III" (manufactured by Beckman Coulter, Inc.), and an optical system such as "SZ-100" (manufactured by Horiba, Ltd.), "ELS-800" (manufactured by Otsuka Electronics Co., Ltd.) which uses the laser Doppler method, or "LB-550" (manufactured by Shimadzu Corporation) which uses the light scattering method.
[0048] The toner of the present invention contains the above polyester resin and a colorant. By using a binder resin containing the polyester resin of the present invention, a toner having excellent chargeability and heat-resistant storage stability can be obtained.
[0049] The toner of the present invention may contain other resins in addition to the polyester resins described above. Any known resins may be used as the other resins, and specific examples of such resins include polyester resins other than the polyester resins described above, vinyl resins, polyurethane resins, epoxy resins, polyamide resins, polyimide resins, silicon resins, phenol resins, melamine resins, urea resins, aniline resins, ionomer resins, and polycarbonate resins. Preferable other resins are polyester resins other than the above polyester resins, vinyl resins, polyurethane resins, epoxy resins and combinations of these, and more preferably polyester resins other than the above polyester resins.
[0050] When the other resin is a polyester resin other than the polyester resin of the present invention, the polyester resin may be a crystalline polyester resin or an amorphous polyester resin, and the same conventionally known alcohol components and / or carboxylic acid components as exemplified for the polyester resin of the present invention can be used. Preferred alcohol components and carboxylic acid components are the same as those for the polyester resin of the present invention described above, and the polyester resin can be produced in the same manner except that a raw material constituting a carboxylate group, a sulfonate group, a sulfamate group, or a phosphate group is not used. In the present invention, "crystalline" refers to a state in which a differential scanning calorimetry (DSC) curve has a maximum and an endothermic peak during the temperature rise process of the differential scanning calorimetry curve obtained by DSC measurement, whereas "amorphous" refers to a state in which the DSC curve does not have an endothermic peak.
[0051] The colorant preferably contains at least one selected from the group consisting of black colorants, blue colorants, red colorants and yellow colorants. As the colorant, any dye, pigment, etc. used as a toner colorant can be used. Specific examples of the pigment include carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Solvent Yellow (21, 77, 114, etc.), Pigment Yellow (12, 14, 17, 83, etc.), India Fast Orange, Irgasin Red, Paranitoaniline Red, Toluidine Red, Solvent Red (17, 49, 128, 5, 13, 22, 48·2, etc.), Disperse Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Solvent Blue (25, 94, 60, 15·3, etc.), Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orasol Brown B, and Oil Pink OP. If necessary, magnetic powder (powders of ferromagnetic metals such as iron, cobalt and nickel, and compounds such as magnetite, hematite and ferrite) may be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 2 to 15 parts by weight, based on 100 parts by weight of the total of the polyester resin of the present invention and other resins. When magnetic powder is used, the content of the magnetic powder is preferably 20 to 150 parts by weight, more preferably 30 to 120 parts by weight, based on 100 parts by weight of the total of the polyester resin of the present invention and other resins.
[0052] The toner of the present invention may contain various known additives such as a releasing agent, a charge control agent, a fluidizing agent, etc., if necessary.
[0053] Examples of the release agent include natural waxes (beeswax, carnauba wax, montan wax, etc.), petroleum waxes (paraffin wax, microcrystalline wax, petrolatum, etc.), synthetic waxes (Fischer-Tropsch wax, polyethylene wax, polypropylene wax, oxidized polyethylene wax, oxidized polypropylene wax, etc.), and synthetic ester waxes (fatty acid esters synthesized from fatty acids having 10 to 30 carbon atoms and alcohols having 10 to 30 carbon atoms, etc.), and it is preferable to contain one or more types selected from the group consisting of these release agents. The content of the release agent is preferably 0 to 30% by weight, more preferably 0.5 to 20% by weight, and even more preferably 1 to 10% by weight, based on 100 parts by weight of the total of the polyester resin of the present invention and other resins.
[0054] When using the above-mentioned release agent, modified wax may be used in combination as necessary. The modified wax is a release agent to which a vinyl polymer chain is grafted. The release agent used in the modified wax may be the same as the above-mentioned release agent, and the preferred ones are also the same. Examples of the vinyl monomer constituting the vinyl polymer chain of the modified wax include styrene and methacrylic acid ester. The vinyl polymer chain may be a homopolymer or copolymer of a vinyl monomer. The content of the modified wax is preferably 0 to 15% by weight, more preferably 0.5 to 10% by weight, and even more preferably 1 to 5% by weight, based on 100 parts by weight of the total of the polyester resin of the present invention and other resins.
[0055] The charge control agent may be either a positively charged charge control agent or a negatively charged charge control agent. Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes having a tertiary amine as a side chain, quaternary ammonium salts, polyamine resins, imidazole derivatives, and quaternary ammonium salts. Examples of the charge control agent include um base-containing polymers, metal-containing azo dyes, copper phthalocyanine dyes, metal salts of salicylic acid, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, halogen-substituted aromatic ring-containing polymers, etc. The content of the charge control agent may be 0 to 20% by weight, preferably 0.1 to 10% by weight, and more preferably 0.5 to 7.5% by weight, based on 100 parts by weight of the total of the polyester resin of the present invention and other resins.
[0056] Examples of the fluidizing agent include silica, titania, alumina, fatty acid metal salts, silicone resin particles, and fluororesin particles, and two or more of them may be used in combination. From the viewpoint of the chargeability of the toner, silica is preferred. From the viewpoint of the transferability of the toner, the silica is preferably hydrophobic. The content of the fluidizing agent may be 0 to 10% by weight, preferably 0 to 5% by weight, and more preferably 0.1 to 4% by weight, based on 100 parts by weight of the toner of the present invention.
[0057] The method for producing the toner is not particularly limited, and the toner may be obtained by a known kneading and grinding method, a suspension polymerization method described in JP-B-36-10231, JP-A-59-53856, and JP-A-59-61842, an emulsion polymerization method represented by a soap-free polymerization method in which a toner is produced by directly polymerizing a monomer in the presence of a water-soluble polymerization initiator that is soluble in the monomer, an interfacial polymerization method such as a microcapsule production method, an in-situ polymerization method, a coacervation method in which at least one type of fine particles is aggregated to obtain a toner of a desired particle size as disclosed in JP-A-62-106473 and JP-A-63-186253, a dispersion polymerization method characterized by monodispersion, a dissolution suspension method in which a necessary resin is dissolved in a water-insoluble organic solvent and then resin particles are formed in an aqueous medium, or an ester elongation polymerization method, or a method in which the toner is dispersed in carbon dioxide in a supercritical state. EXAMPLES
[0058] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these. Example 6 should be read as a Reference Example.
[0059] <Example 1> [Production of Polyester Resin (A-1) and Aqueous Resin Dispersion (D-1)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 256 parts by weight of bisphenol A·PO 2-mol adduct, 191 parts by weight of bisphenol A·PO 3-mol adduct, 256 parts by weight of bisphenol A·EO 2-mol adduct, 10 parts by weight of trimethylolpropane, 277 parts by weight of terephthalic acid, 27 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 11 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was reacted while distilling off the water produced while heating to 220°C under a reduced pressure of 0.5 to 2.5 kPa, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 41 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure and sealed, and then removed to obtain polyester resin (A-1). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-1) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-1) uniformly, obtaining a methyl ethyl ketone solution of (A-1). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-1). The volume average particle size was measured using "SZ-100" and found to be 70 nm.
[0060] <Example 2> [Production of polyester resin (A-2) and aqueous resin dispersion (D-2)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 502 parts by weight of bisphenol A·PO 2-mol adduct, 197 parts by weight of bisphenol A·EO 2-mol adduct, 10 parts by weight of trimethylolpropane, 283 parts by weight of terephthalic acid, 28 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 11 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was reacted while distilling off the water produced while heating to 220°C under a reduced pressure of 0.5 to 2.5 kPa, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 39 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure and sealed, and then removed to obtain polyester resin (A-2). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-2) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-2) uniformly, obtaining a methyl ethyl ketone solution of (A-2). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-2). The volume average particle size was measured using "SZ-100" and found to be 100 nm.
[0061] <Example 3> [Production of polyester resin (A-3) and aqueous resin dispersion (D-3)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 248 parts by weight of bisphenol A·PO 3-mol adduct, 454 parts by weight of bisphenol A·EO 2-mol adduct, 10 parts by weight of trimethylolpropane, 280 parts by weight of terephthalic acid, 28 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 11 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was reacted while distilling off the water produced while heating to 220°C under reduced pressure of 0.5 to 2.5 kPa, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 41 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure and sealed, and then removed to obtain polyester resin (A-3). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-3) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-3) uniformly, obtaining a methyl ethyl ketone solution of (A-3). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-3). The volume average particle size was measured using "SZ-100" and found to be 80 nm.
[0062] <Example 4> [Production of polyester resin (A-4) and aqueous resin dispersion (D-4)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube and a nitrogen inlet tube, 290 parts by weight of bisphenol A·PO 2-mol adduct, 270 parts by weight of bisphenol A·EO 2-mol adduct, 380 parts by weight of propylene glycol, 18 parts by weight of trimethylolpropane, 650 parts by weight of terephthalic acid, 28 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 62 parts by weight of succinic acid and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was reacted while distilling off the water produced while heating to 220°C under reduced pressure of 0.5 to 2.5 kPa, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 41 parts by weight of trimellitic anhydride was added and reacted under normal pressure and sealed for 1 hour, and then removed to obtain polyester resin (A-4). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-4) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-4) uniformly, obtaining a methyl ethyl ketone solution of (A-4). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-4). The volume average particle size was measured using "SZ-100" and found to be 90 nm.
[0063] <Example 5> [Production of polyester resin (A-5) and aqueous resin dispersion (D-5)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube and a nitrogen inlet tube, 380 parts by weight of bisphenol A·PO 2-mol adduct, 400 parts by weight of bisphenol A·EO 2-mol adduct, 180 parts by weight of propylene glycol, 18 parts by weight of trimethylolpropane, 408 parts by weight of terephthalic acid, 27 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 62 parts by weight of succinic acid and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was heated to 220°C under reduced pressure of 0.5 to 2.5 kPa while distilling off the water produced, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 41 parts by weight of trimellitic anhydride was added and reacted under normal pressure and sealed for 1 hour, and then removed to obtain polyester resin (A-5). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-5) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-5) uniformly, obtaining a methyl ethyl ketone solution of (A-5). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-5). The volume average particle size was measured using "SZ-100" and found to be 90 nm.
[0064] <Example 6> [Production of polyester resin (A-6) and aqueous resin dispersion (D-6)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 390 parts by weight of bisphenol A·PO 3-mol adduct, 333 parts by weight of bisphenol A·EO 2-mol adduct, 10 parts by weight of trimethylolpropane, 187 parts by weight of terephthalic acid, 26 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 83 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was reacted while distilling off the water produced while heating to 220°C under a reduced pressure of 0.5 to 2.5 kPa, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 41 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure and sealed, and then removed to obtain polyester resin (A-6). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-6) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-6) uniformly, obtaining a methyl ethyl ketone solution of (A-6). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-6). The volume average particle size was measured using "SZ-100" and found to be 80 nm.
[0065] <Example 7> [Production of polyester resin (A-7) and aqueous resin dispersion (D-7)] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 300 parts by weight of PET flakes (commercially available PET bottles cut into 1 cm squares), 118 parts by weight of propylene glycol, 26 parts by weight of sodium isophthalate dimethyl-5-sulfonate, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added and reacted at 200°C for 3 hours. After cooling to 120°C, 513 parts by weight of bisphenol A·PO 2-mol adduct, 201 parts by weight of bisphenol A·EO 2-mol adduct, 6.0 parts by weight of trimethylolpropane, and 25 parts by weight of succinic acid were added and reacted while distilling off the water produced while heating to 210°C under reduced pressure of 0.5 to 2.5 kPa. When the acid value became less than 2 mgKOH / g, the reaction was cooled to 180°C. Thereafter, 48 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure in a sealed state, and then removed to obtain a polyester resin (A-7). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (A-7) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve polyester resin (A-7) uniformly, obtaining a methyl ethyl ketone solution of (A-7). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (D-7). The volume average particle size was measured using "SZ-100" and found to be 100 nm.
[0066] <Comparative Example 1> [Production of polyester resin (RA-1) and aqueous resin dispersion (RD-1)] In a reaction vessel equipped with a stirrer, heating / cooling device, thermometer, cooling tube, and nitrogen inlet tube, 37 parts by weight of bisphenol A·PO 2-mol adduct, 424 parts by weight of propylene glycol, 466 parts by weight of terephthalic acid, 30 parts by weight of sodium isophthalate dimethyl-5-sulfonate, 59 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was heated to 220°C under reduced pressure of 0.5 to 2.5 kPa while distilling off the water produced, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 43 parts by weight of trimellitic anhydride was added, and the mixture was reacted for 1 hour under normal pressure and sealed, and then removed to obtain polyester resin (RA-1). In addition, 90 parts by weight of methyl ethyl ketone was added to 110 parts by weight of polyester resin (RA-1) in another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer to dissolve it, and then 15.6 parts by weight of sodium hydroxide (10% by weight aqueous solution) was added and stirred at 25°C to dissolve the polyester resin (RA-1) uniformly, obtaining a methyl ethyl ketone solution of (RA-1). 235 parts by weight of water was added to this well-stirred solution to cause phase inversion emulsification, and the methyl ethyl ketone was distilled off to obtain a resin aqueous dispersion (RD-1). The volume average particle size was measured using "SZ-100" and found to be 110 nm.
[0067] The compositions and physical properties of the polyester resin and the aqueous resin dispersion are shown in Table 1.
[0068] [Table 1]
[0069] <Production Example 1> [Production of crystalline polyester resin (C-1) dispersion] In a reaction vessel equipped with a stirrer, a heating / cooling device, a cooling tube, a thermometer, and a nitrogen inlet tube, 683.8 parts by weight of sebacic acid, 436.9 parts by weight of 1,6-hexanediol, and 1 part by weight of titanium dihydroxybis(triethanolamine) as a condensation catalyst were added, and the temperature was raised to 180°C, and the reaction was carried out for 10 hours while distilling off the water generated under a nitrogen stream at the same temperature, and then the reaction was carried out for 4 hours while gradually raising the temperature to 220°C and distilling off the water generated under a nitrogen stream, and further the reaction was carried out while distilling off the water under a reduced pressure of 0.007 to 0.026 MPa, and the reaction was carried out when the acid value became 0.5 mgKOH / g or less. The resin taken out was cooled to room temperature, pulverized and granulated, and a crystalline polyester resin (C-1) was obtained. The melting point was 67°C, the weight average molecular weight was 12,000, and the hydroxyl value was 30 mgKOH / g. Into another reaction vessel equipped with a stirrer, a heating / cooling device, a cooling tube and a thermometer, 30 parts by weight of the obtained crystalline polyester resin (C-1) and 270 parts by weight of ethyl acetate were added, heated to 78°C and stirred at the same temperature for 3 hours, then cooled to 30°C over 1 hour to crystallize the crystalline polyester resin (C-1) into fine particles, which were then wet-pulverized in an Ultraviscomill (manufactured by Imex) to obtain a crystalline polyester resin (C-1) dispersion. The volume-based median diameter of the crystalline polyester resin (C-1) dispersion measured with an "LA-920" was 0.24 μm.
[0070] <Production Example 2> [Production of amorphous polyester resin (E-1) solution] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, a cooling tube, and a nitrogen inlet tube, 263 parts by weight of bisphenol A·PO 2-mol adduct, 197 parts by weight of bisphenol A·PO 3-mol adduct, 264 parts by weight of bisphenol A·EO 2-mol adduct, 10 parts by weight of trimethylolpropane, 259 parts by weight of terephthalic acid, 40 parts by weight of adipic acid, and 3 parts by weight of titanium dihydroxybis(triethanolamine) were added, and the mixture was heated to 220°C under a reduced pressure of 0.5 to 2.5 kPa while distilling off the water produced, and cooled to 180°C when the acid value became less than 2 mgKOH / g. Then, 30 parts by weight of trimellitic anhydride was added, and the mixture was reacted under normal pressure and sealed for 1 hour, and then removed to obtain amorphous polyester resin (E-1). The amorphous polyester resin (E-1) had a number average molecular weight of 2,800, a weight average molecular weight of 10,000, and a glass transition temperature of 58.0°C. Into another reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 250 parts by weight of the obtained amorphous polyester resin (E-1) and 250 parts by weight of ethyl acetate were added and stirred at 25°C to uniformly dissolve the amorphous polyester resin (E-1), thereby obtaining an amorphous polyester resin (E-1) solution.
[0071] <Production Example 3> [Production of modified wax (WD-1)] In a pressure-resistant reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, and a dropping cylinder, 454 parts by weight of xylene and 150 parts by weight of low molecular weight polyethylene "Sanwax LEL-400" [softening point: 128°C, manufactured by Sanyo Chemical Industries, Ltd.] were charged, and after nitrogen replacement, the temperature was raised to 170°C under stirring, and a mixed solution of 595 parts by weight of styrene, 255 parts by weight of methyl methacrylate, 34 parts by weight of di-t-butylperoxyhexahydroterephthalate, and 119 parts by weight of xylene was dropped at the same temperature over 3 hours, and the mixture was maintained at the same temperature for 30 minutes. Next, xylene was distilled off under a reduced pressure of 0.039 MPa to obtain a modified wax (WD-1). The number average molecular weight of the modified wax was 1,900, the weight average molecular weight was 5,200, and the glass transition temperature was 56.9°C.
[0072] <Production Example 4> [Production of release agent dispersion (WO-1)] In a reaction vessel equipped with a cooling tube, a stirrer, a heating / cooling device, and a thermometer, 10 parts by weight of paraffin wax "HNP-9" [melting point: 73°C, manufactured by Nippon Seiro Co., Ltd.], 5 parts by weight of modified wax (WD-1), and 85 parts by weight of ethyl acetate were added, heated to 78°C, and stirred at the same temperature for 3 hours, then cooled to 30°C over 1 hour to crystallize the release agent into fine particles, which were then wet-pulverized with Ultraviscomill (manufactured by Imex) to obtain a release agent dispersion (WO-1). The volume-based median diameter of the release agent dispersion (WO-1) measured with "LA-920" was 0.25 μm.
[0073] <Production Example 5> [Production of Colorant Dispersion (PO-1)] 20 parts by weight of carbon black "MA100" [manufactured by Mitsubishi Chemical Corporation], 4 parts by weight of colorant dispersant "Solsperse 28000" [manufactured by Avecia Corporation], and 56 parts by weight of ethyl acetate were added to a reaction vessel equipped with a stirrer, a heating / cooling device, a cooling tube, and a thermometer, and after stirring to disperse uniformly, the pigment was finely dispersed using a bead mill to obtain colorant dispersion (PO-1). The volume-based median diameter of colorant dispersion (PO-1) measured with "LA-920" was 0.2 μm.
[0074] <Example 8> [Preparation of Toner (T-1)] In a beaker, 135.2 parts by weight of ion-exchanged water, 16.2 parts by weight of resin aqueous dispersion (D-1), 0.4 parts by weight of sodium carboxymethyl cellulose, and 13.2 parts by weight of 48.5% by weight aqueous solution of sodium dodecyl diphenyl ether disulfonate "Eleminol MON-7" [manufactured by Sanyo Chemical Industries, Ltd.] were added, and an aqueous solution was obtained by uniformly mixing. Next, in another container, 105 parts by weight of amorphous polyester resin (E-1) solution, 27 parts by weight of crystalline polyester resin (C-1) dispersion, 14.5 parts by weight of colorant dispersion (PO-1), 10.2 parts by weight of release agent dispersion (WO-1), and 6 parts by weight of ethyl acetate were mixed to obtain a resin solution in which the amorphous polyester resin was dissolved. The entire amount of this resin solution was added to the aqueous solution prepared earlier, and the mixture was stirred for 2 minutes at 10,000 rpm with a TK Auto Homo Mixer [manufactured by Primix Corporation] to obtain a mixed solution. Next, this mixture was transferred to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and ethyl acetate was distilled off until the concentration was 0.5% by weight or less, and the resulting dispersion was washed, filtered, and dried at 40°C for 18 hours to obtain resin particles with a volatile content of 0.5% by weight or less. Next, 100 parts by weight of the resin particles and 1 part by weight of hydrophobic silica "Aerogel R-972" [manufactured by Nippon Aerosil] were uniformly mixed to obtain the toner (T-1) of the present invention.
[0075] <Example 9> A toner (T-2) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-2).
[0076] <Example 10> A toner (T-3) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-3).
[0077] <Example 11> A toner (T-4) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-4).
[0078] <Example 12> A toner (T-5) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-5).
[0079] <Example 13> A toner (T-6) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-6).
[0080] <Example 14> A toner (T-7) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (D-7).
[0081] <Comparative Example 2> A toner (T'-1) was obtained in the same manner as in Example 8, except that the resin aqueous dispersion (D-1) in Example 8 was changed to the resin aqueous dispersion (RD-1).
[0082] Table 2 shows the compositions and evaluation results of the toners obtained in the respective Examples and Comparative Examples.
[0083] [Table 2]
[0084] [Evaluation method] The methods for measuring and evaluating the heat-resistant storage stability and chargeability of the obtained toners (T-1) to (T-7) and (T'-1) will be described below, including the criteria for evaluation.
[0085] <Heat-resistant storage stability> The toners (T-1) to (T-7) and (T'-1) were allowed to stand for 20 hours in an atmosphere of 40°C and a relative humidity of 80%, and the heat resistance storage stability was evaluated according to the degree of blocking and the following criteria. [Evaluation Criteria] ○: No blocking occurs. △: Blocking occurs, but it disperses easily when force is applied. ×: Blocking occurs and the particles do not disperse even when force is applied.
[0086] <Electrostatic properties> 0.5g of toner and 10g of iron powder ("F-150" manufactured by Powder Tech Co., Ltd.) were weighed out and put into a 50cc glass bottle with a stopper, and the bottle was stopped and placed in a Turbula Shaker Mixer (manufactured by Willy-A-Bershoffen Co., Ltd.) in an atmosphere of 23°C and 50% relative humidity, and stirred at 90 rpm for 2 minutes. 0.2g of the mixed powder after stirring was loaded into a blow-off powder charge amount measuring device (TB-203 manufactured by Kyocera Chemical Co., Ltd.) equipped with a stainless steel wire mesh with a mesh size of 20μm, and the charge amount of the remaining iron powder was measured under conditions of a blow pressure of 10KPa and a suction pressure of 5KPa, and the charge amount of the toner (μC / g) was calculated by a standard method. Note that for toner, the higher the negative charge amount, the better the charging characteristics.
[0087] As is clear from the evaluation results in Table 2, the toners (T-1) to (T-7) according to Examples 8 to 14 all achieved excellent results in all performance evaluations. On the other hand, the toner (T'-1) according to Comparative Example 2 was poor in several performance items. [Industrial Applicability]
[0088] The polyester resin of the present invention maintains heat-resistant storage stability and has excellent charging properties, and can be suitably used as a toner for developing electrostatic images in electrophotography, electrostatic recording, electrostatic printing, and the like. Further, it is suitable for use as an additive for paints, an additive for adhesives, particles for electronic paper, and the like.
Claims
1. A polyester resin obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y), the polyester resin being a polyester resin having at least one group selected from the group consisting of a carboxylate group, a sulfonate group, a sulfamate group, and a phosphate group, the valence of the group constituting the carboxylate group, the sulfonate group, the sulfamate group, or the phosphate group being 1, the alcohol component (x) containing an alkylene oxide adduct (x1) of bisphenol A, the (x) of the (x1) being a content in the polyester resin of (x1) is 20 to 98 mol % based on the total number of moles of (x), the (x1) contains an ethylene oxide adduct of bisphenol A (x11) and a propylene oxide adduct of bisphenol A (x12), the molar ratio [(x11) / (x12)] of the ethylene oxide adduct of bisphenol A (x11) to the propylene oxide adduct of bisphenol A (x12) in the (x1) is 30 / 70 to 70 / 30, and the glass transition temperature of the polyester resin is 55 to 85° C.
2. 2. An aqueous resin dispersion comprising fine resin particles containing the polyester resin according to claim 1 dispersed in an aqueous medium.
3. 3. The aqueous resin dispersion according to claim 2, wherein the volume average particle diameter of the resin fine particles is 20 to 500 nm.
4. A toner comprising the polyester resin according to claim 1 or 2 and a colorant.
Citation Information
Patent Citations
Toner for electrostatic image development, method for manufacturing same, electrostatic image developer, and image forming method
JP2007004033A
Resin particle dispersion liquid, method for manufacturing the same, electrostatic charge image developing toner and method for manufacturing the toner, electrostatic charge image developer, and image forming method
JP2008165124A
Dry toner, and developing device, process cartridge, image forming apparatus, and image forming method using the same
JP2009217183A
Polyester resin aqueous dispersion
JP2011046919A
Method for producing polyester, method for producing aqueous dispersion of polyester particles, resin composition, and electrophotographic toner
JP2011148913A